2021
DOI: 10.1021/acs.molpharmaceut.1c00783
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Physicochemical Meaning of a Molecular Descriptor Which Is Predictive of Amorphous Solid Dispersion Formation in Polyvinylpyrrolidone Vinyl Acetate

Abstract: A molecular descriptor known as R3m (the R-GETAWAY third-order autocorrelation index weighted by the atomic mass) was previously identified as capable of grouping members of an 18-compound library of organic molecules that successfully formed amorphous solid dispersions (ASDs) when co-solidified with the co-polymer polyvinylpyrrolidone vinyl acetate (PVPva) at two concentrations using two preparation methods. To clarify the physical meaning of this descriptor, the R3m calculation is examined in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 36 publications
(109 reference statements)
1
31
0
Order By: Relevance
“…Molecular descriptors enable the indirect correlation of desired attributes with a molecule’s structure . Analysis of the structural interpretation of the IFPTML-LDA model showed that total and local linear indices (atom and atom type) are the most influential descriptors in the chemical datasets, specifically nonstochastic matrix orders 2 and 3 in the presence of C atoms in the aliphatic chain.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular descriptors enable the indirect correlation of desired attributes with a molecule’s structure . Analysis of the structural interpretation of the IFPTML-LDA model showed that total and local linear indices (atom and atom type) are the most influential descriptors in the chemical datasets, specifically nonstochastic matrix orders 2 and 3 in the presence of C atoms in the aliphatic chain.…”
Section: Resultsmentioning
confidence: 99%
“…The greater the atomic mass of a halogen, and hence its weight, the more significant its contribution to the descriptor value. Similarly, in the case of the R3m descriptor (R-GETAWAY third-order autocorrelation index weighted by the atomic mass), the presence of atoms heavier than C in a molecule results in a greater contribution to the R3m value [ 8 ]. Note, according to Equation (7), each atom’s contribution to HATS5m depends on both the atom weight (atomic mass in this case) and the leverage.…”
Section: Resultsmentioning
confidence: 99%
“…Consonni and co-workers [ 6 ] proposed a new molecular representation calculated from the spatial coordinates of the molecule atoms in a chosen conformation, allowing for a more accurate similarity/diversity analysis of compounds stored in databases. The development of structure–activity modeling of different biological/physicochemical endpoints confirmed the usefulness of GETAWAY descriptors in molecular sciences [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Several studies prove that the combination of GETAWAY and WHIM descriptors significantly improves the predictive power of the QSAR model [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…8,11,13,14 Typically, hydrogen bonding between drug and polymer makes ASDs more physically stable; 6,8 however, in the case of polyvinylpyrrolidone vinyl acetate random copolymer (PVPVA), molecules such as itraconazole and clotrimazole still form persistent molecular dispersions despite being unable to form hydrogen bonds with the carrier polymer. 15,16 Polymer screening is the first step in preclinical ASD development, 9,17,18 where ruling out drug−polymer compatibility based solely on hydrogen bonding potential overlooks other specific interactions, such as halogen bonds, which may lead to viable formulations. 19 More than 25% of approved FDA drugs contain at least one halogen atom.…”
Section: Introductionmentioning
confidence: 99%